2014
DOI: 10.1186/1756-3305-7-342
|View full text |Cite
|
Sign up to set email alerts
|

Galectin Hco-gal-m from Haemonchus contortus modulates goat monocytes and T cell function in different patterns

Abstract: BackgroundMonocytes and T cells are two major subpopulations of peripheral blood mononuclear cells (PBMC) and play an essential role in the innate and adaptive immune systems. Different members of the galectin family show multiple and distinct regulatory effects on different cell types. Previous studies have demonstrated that the galectin from Haemonchus contortus (Hco-gal-m) performed immunomodulatory effects on goat PBMC, however, which subpopulation of PBMC is the primary target of Hco-gal-m and whether the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 52 publications
4
57
0
Order By: Relevance
“…In our previous studies, we found that recombinant galectin of male and female adult H. contortus displayed different effects on the T cells and monocytes [10, 41]. Thus, it was suspected that the ESPs from males and females also had different functions However, in the natural infection of this worm the ESPs from males and females were secreted and functioned simultaneously.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous studies, we found that recombinant galectin of male and female adult H. contortus displayed different effects on the T cells and monocytes [10, 41]. Thus, it was suspected that the ESPs from males and females also had different functions However, in the natural infection of this worm the ESPs from males and females were secreted and functioned simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…Cell proliferation assay was performed as described previously [10]. Briefly, PBMCs (1 × 10 6 cells/ml) were activated with ConA (10 μg/ml) and incubated at the same time with a serial concentrations of HcESPs (5, 10, 20, and 40μg/ml) and an equal volume of PBS as control at 37°C in 5% CO 2 incubator for 72 h. CCK-8 solutions (Beyotime Biotechnology, China) were added to each well of the plates 4 h before harvesting the cells and the absorbance values at 450 nm (OD 450 ) were measured using a microplate reader (Thermo Scientific, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…El-Sadr et al (1983) showed that canine neutrophils and PBMCs would adhere to, and the neutrophils could kill, D. immitis Mf with the help of IgM from occultly infected animal serum. Parasitic nematodes, including the filaria, secrete a cocktail of immunomodulatory proteins, metabolites and microRNAs which have significant effects on the host immune system (Ashour 2013; Harnett 2014; Harnett and Harnett 2006; Hoerauf et al 2005; McSorley et al 2013; Pineda et al 2014; Wang et al 2014; Buck et al 2014), so it is an obvious speculation that they act to inhibit granulocyte and PBMC binding and antibody-dependent killing of Mf in the infected animal. Another important drug used in the LF elimination programme, diethylcarbamizine (DEC), is believed to exert its anthelmintic effects via activation of the host immune system (Maizels and Denham 1992; Vickery et al 1985), which is consistent with its limited direct effects on nematodes in vitro (Alves et al 2005; Court et al 1986; Gunawardena et al 2005).…”
Section: Is the Host Immune System Involved?mentioning
confidence: 99%
“…The H contortus strain was maintained in the Laboratory of Veterinary Parasitology, Nanjing Agricultural University. H contortus adults were collected as previously described …”
Section: Methodsmentioning
confidence: 99%